Diagnóstico de la atractividad turística del Cantón Yaguachi según la percepción de sus habitantes - Simbaña Rizzo, John Alejandro (2020)
This research Project is aimed at strengthening and determining the importance that the population poses about attractions of the Yaguachi canton where religious, ecological, historical and agrotourist tourism can be developed; where they are used in a sustainable way and disseminated through a tourism marketing plan. It is considered of vital importance to carry out an analysis of the populación’s criteria, to contribute to the tourist development of the Yaguachi canton, improving tourist services, tourist guide establishments, among others, higlighting a benefit for the community. In addition, develop a marketing that frequently promotes outside and within the locality the most important tourist places, and simultaneously the least common. Methods, techniques and instruments were used in order to observe facts and events through surveys and interviews to gather information on the Diagnosis of Tourist Attractiveness of Canton Yaguachi according to the Perception of its Inhabitants, where data was acquired to carry out the tabulation of them and express them in tables and statistical graphs to solve the problema, it was obtained as a conclusión to pormote the development of a tourism product promoting it nationally and internationally. In addition to reforming security measures, providing services in gastronomic, cultural, natural and recreational activities, boosting tourism in Yaguachi.